2017
DOI: 10.1016/j.omtm.2016.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Bringing Neural Cell Therapies to the Clinic: Past and Future Strategies

Abstract: Cell replacement therapy in the nervous system has a rich history, with ∼40 years of research and ∼30 years of clinical experience. There is compelling evidence that appropriate cells can integrate and function in the dysfunctioning human nervous system, but the clinical results are mixed in practice. A number of factors conspire to vary patient outcome: the indication, cell source, patient selection, and team performing transplantation are all variables that can affect efficacy. Most early clinical trials hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 96 publications
0
27
0
Order By: Relevance
“…Another difference from organ transplantation is that healthy cells may be taken from the same person, without a problem of tissue compatibility. [16] On the other hand, cord blood cells can be used for the same purposes. [16] However, cord blood cells also have limited use.…”
Section: ) Embryonic Stem Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another difference from organ transplantation is that healthy cells may be taken from the same person, without a problem of tissue compatibility. [16] On the other hand, cord blood cells can be used for the same purposes. [16] However, cord blood cells also have limited use.…”
Section: ) Embryonic Stem Cellsmentioning
confidence: 99%
“…[16] On the other hand, cord blood cells can be used for the same purposes. [16] However, cord blood cells also have limited use. [16] If the experiments succeed, stem cell therapies will not require extensive surgery or drug administration.…”
Section: ) Embryonic Stem Cellsmentioning
confidence: 99%
“…for cell-based cancer immunotherapy, 62 cardiac cell therapy, 63 islet cell therapy for type II diabetes mellitus, 61 retinal progenitor cell therapy for macular degeneration, 56 hepatocyte cell therapy, 64 cell therapy for the nervous system, 65 and mesenchymal stem cell (MSC) therapy for a wide range of diseases. 66 Consistent with this, forecasts suggest that the number of studies using adult and PSC will continue to grow because of the increasing need for treatments for chronic diseases.…”
Section: Examples Of Cell Therapies Include Chimeric Antigen Receptormentioning
confidence: 99%
“…Only few studies have shown that hMSC-derived neurons are functionally active upon chemical or electrical excitation [21]. Because of the complexity of the nervous system, prior to use hMSC derived neurons as a tool for disease modeling or regenerative applications, the activity pattern and functional synapse formations of these neurons have to be defined to move the neuronal differentiation study a step further [22][23][24].…”
Section: Introductionmentioning
confidence: 99%